2018
DOI: 10.1016/j.jtho.2018.08.894
|View full text |Cite
|
Sign up to set email alerts
|

P1.13-37 Clinical Evaluation of Plasma-Based (cfDNA) Genomic Profiling in Over 1,000 Patients with Advanced Non-Small Cell Lung Cancer

Abstract: Background: Tumor genomic information from a simple blood collection revealing actionable mutation can improve clinical outcome without the need for an invasive tissue biopsy. We report on the clinical utility of a cell-free DNA (cfDNA) next generation sequencing (NGS) blood test in our patients with non-small cell lung cancers (NSCLC) and S596

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The cfDNA test interrogated single-nucleotide variants (SNV) in 73 genes, insertion-deletion (indel) and fusion events, and copy number amplifications in select genes including all eight NCCN guideline-recommended biomarkers as well as KRAS. The cfDNA test has demonstrated extensive analytical and clinical validity and clinical utility (18,(22)(23)(24)(25)30). A clinical report of the cfDNA NGS results was issued to the ordering provider.…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The cfDNA test interrogated single-nucleotide variants (SNV) in 73 genes, insertion-deletion (indel) and fusion events, and copy number amplifications in select genes including all eight NCCN guideline-recommended biomarkers as well as KRAS. The cfDNA test has demonstrated extensive analytical and clinical validity and clinical utility (18,(22)(23)(24)(25)30). A clinical report of the cfDNA NGS results was issued to the ordering provider.…”
Section: Study Proceduresmentioning
confidence: 99%
“…The clinical utility of a predictive biomarker assay is whether it optimizes treatment selection and yields superior outcomes for patients. Multiple head-to-head retrospective studies in aNSCLC have shown that plasma-based CGP leads to treatment outcomes comparable to tissuebased genomic testing, and multiple retrospective analyses revealed that the addition of cfDNA testing increased the identification of driver mutations by 15-65% over SOC tissue-based testing alone at diagnosis (18,(22)(23)(24)(25). Additional prospective studies evaluating plasma-based CGP outcomes in first-line aNSCLC are the global FLAURA (26) trial, the Spanish Lung Liquid vs.…”
Section: Introductionmentioning
confidence: 99%